B-domain deleted factor VIII is aggregated and degraded through proteasomal and lysosomal pathways - Plantier, Jean-Luc; Guillet, Benoit; Ducasse, Cécile; Enjolras, Nathalie; Rodriguez, Marie-Hélène; Rolli, Véronique; Négrier, Claude (Thrombosis and Haemostasis, 2005)
Factor VIII (FVIII) processing within mammalian cells is demonstrated to be much less efficient than proteins of similar size. The deletion of the B-domain from FVIII improves the level of production, due partly to the increase in mRNA synthesis. We aimed to characterise the cellular fate and the intracellular processing of the FVIII molecule devoid of B-domain. A B-domain deleted factor VIII (BDD-FVIII) possessing a furin consensus cleavage site in the connecting segment between the heavy and the light chain, was produced in CHO cell line. In such cells, FVIII was retained as two single chain products from which a majority was aggregated. The two species were located in Triton X-100 soluble (for 60–80%) and insoluble fractions (for 20–40%). The incubation of the expressing cells with tunicamycin (5 μg/ml) and the treatment of the intracellular species with a mixture of Neuraminidase and N-glycosidase-F revealed that both intracellular species were N-glycosylated. Furin over-expression neither diminished the intracellular FVIII contents nor improved its extracellular production. Intracellular FVIII was degraded through both lysosomal and proteasomal pathways as evidenced by inhibitor treatments (e.g. NH4Cl, leupeptin, clasto-Lactacystin β-lactone and MG-132), pulse-chase analysis and confocal observations. This study demonstrates that a BDD-FVIII expressed in CHO cells is inefficiently processed consecutively to intracellular aggregation, proteasomal degradation, and routage to lysosomes.
Keywords: Degradation; factor VIII; furin; lysosome